The Effect of Gallery Walk Technique on Students’ Speaking Skill - Linda Astuti Rangkuti; Meida Rabia Sihite; Jatra Jatra (Journal of English Language and Education, 2022)
The objective of this research is to investigate if Gallery Walk Technique significantly affects students’ speaking skill. The design used in this research was experimental research design. The population of this research was the students of grade X of SMA Pelita Bulu Cina. The total number of the population was 30 students. Cluster sampling technique was used in drawing the sample. So, 15 students were selected into the experimental group (X-I) and 15 students were selected into control group (X-II). Speaking test was used as the instrument of this research. The data were analysed by using Mann Whitney U-test formula. It was found that the smaller U-observed value was 1. It was smaller than U-table value which was 64 at p = 0,05 (1 64). Thus, Ha was accepted and Ho was successfully rejected. Thus, Gallery Walk Technique significantly affects students’ speaking skill.